Use of mixtures of herbicides in rubber tree plantations in formation - Soares, Welington Oliveira; Cunha, Raimundo L. Moraes da; M. Viégas, Ismael de Jesus; F. Viégas, Rosemary Moraes (Pesquisa Agropecuaria Brasileira, 2014)
Two herbicides, MSMA and paraguat, applied as post-emergents, were tested singly and in association with five other herbicides: diuron, prometone, tebutiuron, etidimuron and simazine. These were compared among themselves and with manual weeding by machete, as to their efficiencies in weed control. The mixtures were always superior in effectiveness, and among these the following gave the best results: MSMA + diuron (1957+1600) g a.i/ha; paraquat + diuron (400+1600) g a.i./ha; MSMA + etidimuron (1957+2100) g a.i/ha; and, paraquat+ etidimuron (400+2100g a.i./ha. Among these, the first two were most economical in addition to being available on the commercial market.
Keywords: Hevea spp.; weeds; chemical control